ANALISIS KELAYAKAN USAHA PETERNAKAN PUYUH PETELUR (Coturnix coturnix japonica) DI DESA ASAM PEUTIK KECAMATAN LANGSA LAMA (STUDI KASUS : USAHA PETERNAKAN PUYUH PETELUR IBU JUMIANI) - Sinta Dewi; Rozalina; Kiagus M. Zain Basriwijaya (Jurnal Cakrawala Ilmiah, 2023)
This study aims to analyze the feasibility of laying quail farming by Mrs. Jumiani in Asam Peutik Village, Langsa Lama District. The sampling technique used purposive sampling technique with a sample of 1 person. The data used in this study are primary data and secondary data. To find out the feasibility of laying quail farming by Mrs. Jumiani in Asam Peutik Village, Langsa District, a feasibility analysis was carried out, namely Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP) and R/C Ratio. The results of this study obtained a Net Present Value (NPV) of Rp53.848.834 with NPV criteria > 0 then the business is feasible. Internal Rate Return (IRR) 54,22% with the criteria IRR> DR (6%) then the business is feasible to run. R/C Ratio of Rp2,98 with the criteria of R/C Ratio > 1 then the business is feasible to run. From the three calculations, the feasibility analysis shows that the results of the laying quail farm of Mrs. Jumiani in Asam Peutik Village, Langsa Lama District are feasible to be cultivated and the Payback Period (PP) is 0,3 years or 3,5 months, which is smaller than the project age of 1,5 years or 18 months, which means that within 0,3 years or 3,5 months the business is able to return investment costs before the productive time of the business.